People's Republic of China : Detailed Assessment Report: Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2012)
A detailed assessment report on the observance of China's compliance of Basel Core Principles for effective banking supervision is presented. Regulation and supervision of China's banking system has made impressive progress in the past few years, led by an activist, forward-looking regulator, the China Banking Regulatory Commission, with a clear safety and soundness mandate that has been supported by banks and by the State. The macroeconomic environment is characterized by rapid growth, with concerns about overheating and asset price overvaluation.